2023
DOI: 10.3390/ijerph20105840
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness before and after COVID-19: Sense of Coherence and Hope as Coping Mechanisms

Abstract: The COVID-19 pandemic posed a major threat to public health, with long-lasting consequences for the daily habits and practices of people around the world. The combination of hazardous health conditions and extensive changes to people’s daily routines due to lockdowns, social restrictions, and employment uncertainty have led to mental health challenges, reduced levels of subjective wellbeing, and increased maladaptive behaviors and emotional distress. Nevertheless, some studies have reported increased adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
3
4
1
Order By: Relevance
“…Moreover, our results show a significant increase in both social and emotional loneliness from the period when the COVID-19 pandemic began until 2021. Similar initial increases in loneliness are also documented in other studies [7,11,12,22] and can be understood in the context of the measures taken to prevent the spread of COVID-19 at that time, which directly impacted social relationships. Even though technology tried to compensate for the lack of personal social contacts, interactions via technology did not protect against feelings of loneliness [27,28].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, our results show a significant increase in both social and emotional loneliness from the period when the COVID-19 pandemic began until 2021. Similar initial increases in loneliness are also documented in other studies [7,11,12,22] and can be understood in the context of the measures taken to prevent the spread of COVID-19 at that time, which directly impacted social relationships. Even though technology tried to compensate for the lack of personal social contacts, interactions via technology did not protect against feelings of loneliness [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…In the UK, Carollo and colleagues [11] observed a U-shaped pattern indicating higher levels of loneliness in the first weeks of lockdown, followed by a decrease in loneliness in the weeks 4-6, and a subsequent increase in loneliness in the following weeks. Studying two different Israeli samples, Einav & Margalit [12] found an increase in loneliness after the COVID-19 pandemic. In Slovenia, Gomboc and colleagues [7] used a similar research design to compare two different samples and found an increase in emotional loneliness (related to the quality of relationships) but a decrease in social loneliness (related to the quantity of relationships).…”
Section: Introductionmentioning
confidence: 99%
“…This result supports previous studies that identified geographic variations in risk perception [8]. This Ontario-specific vulnerability is likely to be multifactorial in nature, with variables such as epidemiological factors (e.g., higher population densities, differential infection rates) and the stringency of the lockdown measures (with social isolation being associated with poorer emotional well-being; [54]). Those with a poor health status were more likely to experience COVID-19-related distress, which is likely due to a combination of higher physical vulnerability and the health threat of contracting COVID-19, with these factors being compounded by the limited access to healthcare experienced by Chinese individuals in Ontario [23,55].…”
Section: Sociodemographic Predictorssupporting
confidence: 88%
“…It is well known that anxiety is common in older adulthood, probably even underestimated since little is known about assessment of anxiety later in life (37), and adding to this underlying condition could be the context of living in a pandemic with fear of the virus, and social isolation (19,38,39). During such conditions belief and hope for the future might be more di cult to sustain but it has been described as a resilience factor when coping with stress, promoting well-being (40). This present study revealed some increase towards a pessimistic belief for the future during the pandemic compared to pre-pandemic, but not signi cantly (data not shown).…”
Section: Discussioncontrasting
confidence: 51%